2021
DOI: 10.1098/rspb.2021.0774
|View full text |Cite
|
Sign up to set email alerts
|

Noise matters: elephants show risk-avoidance behaviour in response to human-generated seismic cues

Abstract: African elephants ( Loxodonta africana ) use many sensory modes to gather information about their environment, including the detection of seismic, or ground-based, vibrations. Seismic information is known to include elephant-generated signals, but also potentially encompasses biotic cues that are commonly referred to as ‘noise’. To investigate seismic information transfer in elephants beyond communication, here we tested the hypothesis that wild elephants detect and discriminate between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…163 More recent studies have identified the social and environmental monitoring purposes associated with this communication channel in elephants. [164][165][166] Anti-predatory structures and strategies It is thought that the origin of many distinctive morphological and/or behavioral traits of living organisms is related to the selective pressure exerted by for the multipletarget illusion. An enlarged echo illusion would likely lead bats to target the hindwing just behind the abdomen of the moth, at the perceived echo center (highlighted in green); however, bats targeted this region only 25% of the time (adapted from Rubin et al 171 ).…”
Section: Scorpion Sensingmentioning
confidence: 99%
“…163 More recent studies have identified the social and environmental monitoring purposes associated with this communication channel in elephants. [164][165][166] Anti-predatory structures and strategies It is thought that the origin of many distinctive morphological and/or behavioral traits of living organisms is related to the selective pressure exerted by for the multipletarget illusion. An enlarged echo illusion would likely lead bats to target the hindwing just behind the abdomen of the moth, at the perceived echo center (highlighted in green); however, bats targeted this region only 25% of the time (adapted from Rubin et al 171 ).…”
Section: Scorpion Sensingmentioning
confidence: 99%
“…Current natural vibrational communities may already have been altered due to habitat loss and fragmentation, biological invasion, climate change and anthropogenic noise. Although there is so far no information on the impact of human activities on vibroscapes, field studies of the effects of anthropogenic vibrations showed negative effects on animal behavior (Shier et al, 2012;Day et al, 2019;Phillips et al, 2020;Mortimer et al, 2021;Roberts and Howard, 2022). The recording of pristine and disturbed vibroscapes appears as a prerequisite for future work; however, there is also a need to build reference libraries and baseline information to assess the possible future changes of vibroscapes.…”
Section: Link Between Vibroscape Composition and Ecosystem Statementioning
confidence: 99%
“…Pensémoslo de otro modo. Estudios recientes han mostrado indicios de que los elefantes africanos son susceptibles a diferentes clases de ruidos sísmicos y son incluso capaces de categorizarlos, hasta el punto de responder ante ellos distintivamente, "en algunos casos con respuestas basadas en la aversión al riesgo" y en correlación con "un incremento de la presencia de hormonas del estrés" 79 . Incluyendo la posibilidad de que existan errores de atribución -por los que las pistas sísmicas sean mal interpretadas en cuanto a su origen-, lo cierto es que no se recoge la posibilidad de que se mantengan en el mismo sitio por mor de la contemplación estética.…”
Section: La Variante Estética De Tennantunclassified